Analisis Persaingan Dan Kepuasan Konsumen Dengan Menggunakan Metode Correspondance Analysis Dan Importance Performance Analysis - Nanda Bagus Pratama; Shanty Kusuma Dewi; Teguh Baroto (Jurnal Teknik Industri, 2015)
Epic Culinary is a cafe and a restaurant that established in January 2015. According to a survey conducted at the beginning of Epic Culinary it can be seen that the problems faced by the existence of a complaint to the problem places, products, facilities, and price. In addition, as a company that is growing and developing Epic Culinary do not have characteristics of companies that made the difference with existing competitors. Of the problems faced by the company companies also need to consider existing competitors, both in terms of strengths and weaknesse. In addition to analyzing the company's existing competitors should also strive to realize the expectations of consumers. Correspondence Analysis (CA) is the method used to pay attention to competitors, namely in terms of strengths and weaknesses of the company which will then be made as input in designing a strategy. After that to determine the extent of quality of service the company has done to the satisfaction of customer dan to increase consumer loyalty is by using importance performance analysis (IPA). Application of the method both methods above will do the deployment questionnaire using 7P concept of product, price, place, promotion, people, physical evidence and process used as an attribute in making the questions.